About applying directly the alpha finite element method (\(α\)FEM) for solid mechanics using triangular and tetrahedral elements - Trung, Nguyen Thoi; Hung, Nguyen Xuan (Vietnam Journal of Mechanics, 2010)
An alpha finite element method (\(α\)FEM) has been recently proposed to compute nearly exact solution in strain energy for solid mechanics problems using three-node triangular (\(α\)FEM-T3) and four-node tetrahedral (\(α\)FEM-T4) elements. In the \(α\)FEM, a scale factor \(α \in [0, 1]\) is used to combine the standard fully compatible model of the FEM with a quasi-equilibrium model of the node-based smoothed FEM (NS-FEM). This novel combination of the FEM and NS-FEM makes the best use of the upper bound property of the NS-FEM and the lower bound property of the standard FEM. This paper concentrates on applying directly the \(α\)FEM for solid mechanics to obtain the very accurate solutions with a suitable computational cost by using \(α = 0.6\) for 2D problems and \(α = 0.7\) for 3D problems.